A hepatitis A, B, C and HIV prevalence and risk factor study in ever injecting and non-injecting drug users in Luxembourg associated with HAV and HBV immunisations - Schmit Jean-Claude; Vaillant Michel; Couffignal Sophie; Origer Alain; Removille Nathalie; Lair Marie-Lise (BMC, 2011)
Abstract Background In Luxembourg, viral hepatitis and HIV infection data in problem drug users (PDUs) are primarily based on self-reporting. Our study aimed to determine the prevalence of HAV, HBV, HCV and HIV infections in ever injecting (IDUs) and non-injecting drug users (nIDUs) including inherent risk factors analysis for IDUs. Secondary objectives were immunisation against HAV and HBV, referral to care and treatment facilities as well as reduction in risk behaviour. Methods A nationwide, cross-sectional multi-site survey, involving 5 in-, 8 out-treatment and 2 prison centres, included both an assisted questionnaire (n = 368) and serological detection of HIV and Hepatitis A, B, C (n = 334). A response rate of 31% resulted in the participation of 310 IDUs and 58 nIDUs. Risk factors such as drug use, sexual behaviour, imprisonment, protection and health knowledge (HAV, HBV status and immunisations, HCV, HIV), piercing/tattoo and use of social and medical services were studied by means of chi2 and logistic models. Results Seroprevalence results for IDUs were 81.3% (218/268, 95%CI=[76.6; 86.0]) for HCV, 29.1% (74/254, 95%CI=[25.5;34.7 ]) for HBV (acute/chronic infection or past cured infection), 2.5% (5/202, 95%CI=[0.3; 4.6]) for HIV-1 and 57.1% (108/189, 95%CI=[50.0; 64.1]) for HAV (cured infections or past vaccinations). Seroprevalence results for nIDUs were 19.1% (9/47, 95%CI=[7.9;30.3]) for HCV, 8.9% (4/45, 95%CI=[0.6;17.2]) for HBV (acute/chronic infection or past cured infection), 4.8% (2/42, 95%CI=[-1.7;11.3]) for HIV-1 and 65.9% (27/41, 95%CI=[51.4;80.4]) for HAV. Prisoners showed the highest rates for all infections. Age, imprisonment and setting of recruitment were statistically associated with HCV seropositivity. Age, speedball career and nationality were significantly associated with HBV seropositivity. Only 56% of the participants in outpatient centres collected their serology results and 43 doses of vaccine against HAV and/or HBV were administered. Conclusions Despite the existing national risk-reduction strategies implemented since 1993, high prevalence of HCV and HBV infections in injecting drug users is observed. Our study showed that implementing risk-prevention strategies, including immunisation remains difficult with PDUs. Improvement should be looked for by the provision of field healthcare structures providing tests with immediate results, advice, immunisation or treatment if appropriate.